2018
DOI: 10.1038/modpathol.2017.128
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clinically relevant somatic mutations in high-risk head and neck cutaneous squamous cell carcinoma

Abstract: Cutaneous squamous cell carcinoma is the second most prevalent malignancy, most frequently occurring in the head and neck (head and neck cutaneous squamous cell carcinoma). Treatment of locally advanced or metastatic disease is associated with functional morbidity and disfigurement. Underlying genetic mechanisms are poorly understood. Targeted sequencing of 48 clinically relevant genes was performed on DNA extracted from formalin-fixed and paraffin-embedded high-risk primary head and neck cutaneous squamous ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 53 publications
(57 reference statements)
1
34
0
Order By: Relevance
“…While whole genome and whole exome studies produce significantly larger amounts of data, use of a clinically relevant gene panel that encompasses the current therapeutic armamentarium ensures reproducibility, cost effectivity and rapid translation. This study expands on previous work by Zilberg et al 3 and assesses genetic alterations in high risk HNcSCC present at variant allele frequencies (VAFs) >1% for suitability of targeted therapies in light of the current literature demonstrating response, as well resistance, to targeted therapies at VAFs<5% of the implicated mutation 4…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…While whole genome and whole exome studies produce significantly larger amounts of data, use of a clinically relevant gene panel that encompasses the current therapeutic armamentarium ensures reproducibility, cost effectivity and rapid translation. This study expands on previous work by Zilberg et al 3 and assesses genetic alterations in high risk HNcSCC present at variant allele frequencies (VAFs) >1% for suitability of targeted therapies in light of the current literature demonstrating response, as well resistance, to targeted therapies at VAFs<5% of the implicated mutation 4…”
Section: Introductionsupporting
confidence: 55%
“…Patient selection and sample preparation were performed as per Zilberg et al 3. High-risk characteristics were defined as per the seventh edition of the American Joint Committee on Cancer Staging (AJCC) Manual 6.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 We have recently identified alterations in MLH1 genes in two young (<45 years of age) cSCC patients using Illumina TruSeq 48 gene panel. 6 Meira et al 7 have demonstrated MSH2-null mice to have an increased predisposition to UVB induced tumors with onset of tumors at lower dosage of UVB and more aggressive progression. MSI and MMR alterations are well described in sebaceous neoplasms in Muir-Torre syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, compared with NTRK-wt group, APC and PTPRD mutations were more common in NTRK-GA group. APC and PTPRD have been reported to associated with inferior outcome of HNSCC [42,43]. The potential interactions between these two genes and NTRK aberrations need further study.…”
Section: Discussionmentioning
confidence: 98%